Copper and zinc adsorption by softwood and hardwood biochars under elevated sulphate-induced salinity and acidic pH conditions. (January 2016) - Jiang, Shasha; Huang, Longbin; Nguyen, Tuan A.H.; Ok, Yong Sik; Rudolph, Victor; Yang, Hong; Zhang, Dongke
Highlights: Hardwood jarrah biochar adsorbed more Cu and Zn than softwood pine biochar. Jarrah biochar exhibited higher micropore surface area and surface alkalinity. Elevated sulphate-salinity had weak effects on Cu and Zn adsorption by the biochars. Raising pH to 6 lowered biochar surface charges and increased Cu and Zn adsorption. Abstract: Biochar adsorption may lower concentrations of soluble metals in pore water of sulphidic Cu/Pb–Zn mine tailings. Unlike soil, high levels of salinity and soluble cations are present in tailing pore water, which may affect biochar adsorption of metals from solution. In the present study, removal of soluble copper (Cu) and zinc (Zn) ions by soft- (pine) and hard-wood (jarrah) biochars pyrolysed at high temperature (about 700 °C) was evaluated under typical ranges of pH and salinity conditions resembling those in pore water of sulphidic tailings, prior to their direct application into the tailings. Surface alkalinity, cation exchange capacity, and negative surface charge of biochars affected Cu and Zn adsorption capacities. Quantitative comparisons were provided by fitting the adsorption equilibrium data with either the homogeneous or heterogeneous surface adsorption models (i.e. Langmuir and Freundlich, respectively). Accordingly, the jarrah biochar showed higher Cu and Zn adsorption capacity ( Q max = 4.39 and 2.31 mg/g, respectively) than the softwood pine biochar ( Q max = 1.47 and 1.00 mg/g). Copper and Zn adsorption by the biochars was favoured by high pH conditions under which they carried more negative charges and Cu and Zn ions were predicted undergoing hydrolysis and polymerization. Within the tested range, salinity had relatively weak effects on the adsorption, which perhaps influenced the surface charge and induced competition for negative charged sites between Na + and exchangeable Ca 2+ and/or heavy metal ions. Large amounts of waste wood/timber at many mine sites present a cost-effective opportunity to produce biochars for remediation of sulphidic tailings and seepage water.